ANALISIS BIBLIOMETRIK PENELITIAN PENGGUNAAN AGREGAT DAUR ULANG DALAM BETON BERPORI TREN DAN PERKEMBANGAN 2019-2024 - Noorfauzi, Ahmad Ridhani; Kurniawan, Budi; Nabillah, Jihan Alya (Politeknik Negeri Jakarta, 2025)
This research was conducted to present a comprehensive bibliometric analysis of research trends and developments using recycled aggregates in pervious concrete from 2019 to 2024. The Publish or Perish application was used to collect bibliometric data from Google Scholar metadata relevant to the research topic. Publish or Perish is free software with a non-commercial license issued by its developer and used for academic purposes. 200 relevant publications were analysed to identify research patterns, collaboration networks, and emerging topics in this field. The results show a fluctuating but generally increasing trend in publications, with the highest activity in 2020 (43 publications) and sustained interest through 2023 (39 publications). Recycled Concrete Aggregate (RCA) emerged as the dominant research focus (22% of material-specific studies), followed by industrial waste materials (11%). The network analysis reveals increased international collaboration and a greater focus on sustainability aspects. This study identified major clusters of research on mechanical properties, durability, and permeability optimization. Through the analysis, important insights are presented for sustainable construction researchers and practitioners with the progress that has been made, as well as areas that require further investigation in the development of pervious concrete made from recycled materials.